Konstruksi dan Negosiasi Interseksionalitas dalam Seperti Dendam, Rindu Harus Dibayar Tuntas serta Implikasi Sugestif Nilai Pendidikan - Ilaturahmi, Auzi (Jurnal Bahasa dan Sastra, 2025)
The study that wants to be analyzed is how the construction and negotiation of intersectionality are built in “Seperti Dendam, Rindu Harus Dibayar Tuntas” and the suggestive implications of educational values. Therefore, the mimetic approach is used as the basis for analysis in this study. The social reality related to intersectionality reflected by the author in his novel entitled " Seperti Dendam, Rindu Harus Dibayar Tuntas " is explored using a descriptive method. This method seeks to explore phrases, words, sentences, and discourses from the speech of characters and narrators that describe the attitude of intersectionality in the novel "Seperti Dendam, Rindu Harus Dibayar Tuntas" by Eka Kurniawan. Then, the implications of the suggestive analysis become educational values. This is so important because literary works should contain something that can be learned from. The results of the analysis are the discovery of three principles that are directly related to the theory of intersectionality in the novel "Like Revenge, Rindu Must Be Paid in Full", namely multiple identities, layered discrimination, and systemic injustice. The construction of a male image in the novel is based on these three principles. This implies that men are the ones who hold the control and power of life so that they are arbitrary towards the group that is considered weak, namely women. In addition, in the midst of the poor view of intersectionality in the novel “Seperti Dendam, Rindu Harus Dibayar Tuntas”, integrative negotiation is also presented to color the storyline. The construction and negotiation bring us to the conclusion of educational values, namely the competence and character of individuals personally and socially. The personal competence of individuals that can be suggested is accountable and loyal. Meanwhile, the social competence of individuals that is suggested is service-oriented and harmonious.